The Role of Islam on Dysphemia And Its Relation to Language Logic - Alfitri, Nadia; Nurfatoni, Rizhal Azhar (Program Pascasarjana UIN Sumatera Utara, 2024)
Times are changing, technology is developing, humans are becoming more advanced. Many changes are caused by advances in time, technology and humans. The most visible changes are people's attitudes and behavior which have changed a lot, one of the changes in society is negative speech and language because there are many factors that influence it. Factors that can influence people's behavior and attitudes, especially speech and language, include the influence of social media, the relationship between a person and their friends, lack of mastery of the language, and lack of previous religious education. Among the many things that influence speech and language, a person's experiences have a major impact on a person's personality and character. Especially in social life. Educational background and also the environmental background where you live play an important role in influencing the way you behave, think and also speak. External factors here are able to influence a person more than internal factors. However, we can control this, one of the ways is by being equipped with religious knowledge that contains this matter. No matter how serious a bad habit is, it will not affect or change a person's behavior if the person tries hard not to do these things. The use of the word dysphemia depends on a person's ability to think and use logic in language. The word dysphemia emphasizes poor use of language in language. This research aims to understand language from an Islamic perspective that contains elements of dysphemia.Zaman semakin berubah, teknologi semakin berkembang, manusia semakin maju. Banyak perubahan yang diakibatkan oleh kemajuan zaman, teknologi dan manusia. Perubahan yang paling terlihat adalah sikap dan perilaku masyarakat yang banyak berubah, salah satu perubahan masyarakat adalah tutur kata dan bahasa yang negatif karena banyak faktor yang memengaruhinya. Faktor-faktor yang dapat mempengaruhi perilaku dan sikap masyarakat khususnya tutur kata dan bahasa antara lain, pengaruh media sosial, hubungan antara seseorang dengan teman-temannya, kurang menguasai bahasa, dan kurangnya pendidikan agama sebelumnya. Di antara banyak hal yang memengaruhi ucapan dan bahasa, pengalaman seseorang mempunyai dampak yang besar terhadap kepribadian dan karakter seseorang. Khususnya dalam kehidupan bersosial. Latar belakang pendidikan dan juga latar belakang lingkunagn tempat tinggal mengambil peranan penting dalam memengaruhi cara bersikap, berpikir dan juga berbahasa. Faktor eksternal disini mampu memengaruhi seseorang lebih dari faktor internalnya. Akan tetapi hal tersebut dapat kita kendalikan salah satunya dengan dibekali ilmu agama yang memuat tentang hal tersebut. Betapapun seriusnya kebiasaan buruk, tidak akan mempengaruhi atau mengubah perilaku seseorang jika orang tersebut berusaha keras untuk tidak melakukan hal-hal tersebut. Penggunaan kata disfemia ini bergantung pada kemampuan berpikir dan penggunaan logika dalam berbahasa seseorang. kata disfemia ini menekankan pada penggunaan bahasa yang kurang baik dalam berbahasa, penelitian ini bermaksud untuk memahami bahasa dalam pandangan Islam yang mengandung unsur disfemia.